Protection of Consumer Rights in Online Transactions from the Perspective of Positive Law on Consumer Protection and the Compilation of Sharia Economic Law - Saeful Anwar; Sri Rokhilnasari; Ayus Ahmad Yusuf; Irfan Azis (Eduvest - Journal of Universal Studies, 2024)
This research is motivated by a phenomenon that business actors in buying and selling online often provide unclear information. This research is a library research on consumer legal protection in online buying and selling according to Law No. 8 of 1999 and consumer protection in online buying and selling according to the Compilation of Sharia Economic Law and comparison of consumer protection in online buying and selling according to UUPK and KHES. The results showed that, Legal protection of consumers in online buying and selling according to Law No. 8 of 1999 is not fully realized, because many consumer rights are violated by online business actors. Violated consumer rights are contained in GCPL Article 4, Article 7, Article 8, Article 17, Article 19. The legal protection of consumers in online buying and selling based on the Compilation of Sharia Economic Law is the provision of protection in the form of khiyar rights (cancel or continue the sale and purchase contract). The similarity of consumer legal protection in online buying and selling according to GCPL and KHES is that they must provide correct, clear, and honest information about the conditions and guarantees of goods and / or services. While the difference in consumer protection in online buying and selling according to GCPL and KHES is that according to GCPL, administrative sanctions and criminal sanctions are imposed; in KHES, consumers are given the right to khiyar (cancel or continue the contract) in online buying and selling.